Association Between Knowledge, Attitudes and Practices (KAP) Towards The COVID-19: A Cross-Sectional Study in South Korea - Lee, Minjung; Kang, Bee-Ah; You, Myoungsoon (BMC Public Health, 2020)
Background It is imperative for the public to routinely practice precautionary behaviors to contain transmission of COVID-19, as no vaccines and anti-viral treatments are available. This paper attempts to examine knowledge, attitudes, and practices related to COVID-19, and the relationship between them and identification of the vulnerable population. Methods The data collection took place over three days (June 26–29) through an online survey five months after the Korea Centers for Disease Control and Prevention (KCDC) confirmed the first case in South Korea; 970 subjects were included in the analysis. Results The level of knowledge, attitude and practice were examined. Knowledge directly affected both attitude (e.g., perceived risk and efficacy belief) and practice (e.g., preventive measures and social distancing). Among the influencing factors, efficacy belief turns out to be the most effective and significant factor on practice and also mediated the relationship between knowledge and all three preventive behaviors (wearing facial masks, practicing hand hygiene, and avoiding crowded places). Knowledge level varied by sociodemographic characteristics. Females (β = 0.06, p < 0.05) and individuals with higher level of education (β = 0.06, p < 0.05) had higher knowledge. Conclusion To successfully increase precautionary behaviors among the public, public health officials and policy makers must promote knowledge and efficacy belief. Also, the consequent interventions and policies should be developed and implemented in a way they reduce, rather than reinforce, health disparities, by embracing vulnerable populations to COVID-19.